Dynamic bias-temperature instability study of metal/high-K gate stacks - Gao, Yuan (2014)
In summary, a systematic study on the dynamic BTI of the metal/high-k gate stacks is conducted. The evolution of the switching oxide traps under the NBT and PBT stressing are compared and the possible oxygen defect framework is proposed. The frequency dependence of the BTI recovery is also examined. Implications of these new experimental observations on the device reliability assessment and modeling are discussed.